What is the impact of social activist movements like Fees Must Fall on the brand health of the University of Cape Town? - Pangalele, Tanya (The IIE, 2017)
Much has been written about the Fees Must Fall Movement that took place in South Africa over last two years. These written pieces were often through the lenses of the media, opinion pieces and social media commentary. These articles often focus on the institutional damage, the violence, the widespread protests and the governmental effect and involvement – the core issue at hand - the ever increasing higher education Fees in South African. These written pieces have focused on many sides of the debate, with media and thought leaders choosing to look at the impact on the students itself, or the impact of governments’ way of addressing the issue, or how the institutions themselves are dealing with the issue and who are what forces are at play in this rising issue. As a result, based on the aforementioned information, an opportunity to explore the impact that Fees Must Fall has had on, in particular, the University of Cape Town (UCT) has been identified. This research report focusses on the impact of a movement like Fees Must Fall has had on UCT and seeks to explore the brand health impact. The research thus is considered an exploratory study that uses in-depth interviews using qualitative research. The data from the research was analysed in depth by the researcher.
Keywords: Protests; Social Media; Brand Image; Higher Education; Higher Education Institutions; Brand Health; Brand Activism; Social Activism; Brand Equity